Development of an Assessment Tool for Green Project Skills in Project-Based Steam Learning Integrated with the BCG Economy Model - Ruengrung, Sathaphorn; Wuttiprom, Sura; Wuttisela, Karntarat; Lateh, Afifi (Journal of Graduate Research, 2026)
This research aimed to 1) synthesize the components of green project skills and 2) develop and examine the quality of an assessment tool for evaluating these skills in project-based STEAM learning activities integrated with the BCG Economy Model. The participants consisted of 1) nine experts holding doctoral degrees in Science Education, Curriculum and Instruction, or Educational Measurement and Evaluation, with research experience in STEM or STEAM education; and 2) two project evaluators holding bachelor’s degrees with more than five years of experience as advisors for science and vocational projects. The research instruments included 1) a document synthesis form, 2) a content validity assessment form, and 3) a pilot version of the green project skills assessment tool. All instruments were preliminarily reviewed by three thesis advisory committee members. Data were collected through document synthesis and the identification of key components using content analysis based on keyword frequency and thematic categorization. The quality of the assessment tool was examined in terms of content validity and inter-rater reliability. The findings revealed that: 1) green project skills consist of three components: (1.1) the ability to analyze the content and context of green projects, (1.2) practical competence in conducting green projects, and (1.3) the ability to present green projects; and 2) the developed assessment tool is a three-level analytic rubric comprising 21 items. The content validity index (CVI) ranged from 0.78 to 1.00, and the scale-level CVI (S-CVI/Ave) was 0.91, exceeding the acceptable threshold. The inter-rater reliability, analyzed between the two evaluators, yielded a Cohen’s kappa coefficient of 0.78, indicating a moderate level of agreement, although the percentage of agreement ranged from 36% to 63%.